Empirical research in law. Issue 2 (2nd April 2016) - Bell, Felicity
ABSTRACT: Undertaking empirical research in law can be a daunting task, one for which current undergraduate and postgraduate legal education does not provide a great deal of preparation. Yet the ability to undertake such research is valuable and, some suggest, in demand. Many areas of law, its operation and effects, can be usefully informed by empirical research. This article suggests that the benefits of empiricism are both pragmatic or policy-driven, and theoretical.